Authentic Leadership, Organizational Citizenship Behavior, dan Keadilan Organisasi sebagai Pendorong Kepuasan Kerja: Bukti pada Perusahaan Manufaktur di Indonesia - Bisma Anjala Sutra; Alfato Yusnar Kharismasyah; Naelati Tubastuvi; Suyoto (Nur Science Institute, 2026)
This research aims to examine the influence of Authentic Leadership, Organizational Citizenship Behavior, and Organizational Justice on Job Satisfaction. The population in this study was employees of PT. Sumber Graha Sejahtera Purbalingga. This study used a non-probability sampling technique with a purposive sampling approach. The determination of the number of samples was carried out using the Slovin formula, with a population of 864 employees and a tolerance level of error of 10%, resulting in an initial sample of 90 respondents. The classification of information in this investigation was firsthand information in the form of a questionnaire using a 1–5-point Likert scale. Meanwhile, the data testing procedure applied was SmartPLS 3.2.9. The results of the analysis showed that Authentic Leadership and Organizational Justice had a positive and significant influence on Job Satisfaction. This study also revealed that OCB was not significant for job satisfaction. The implications of this article indicate that the results of the study indicate that the results of the study can be a reference for organizations in improving employee satisfaction and performance through the implementation of appropriate leadership, increasing organizational justice, and strengthening positive behaviors such as OCB.